PEMEROLEHAN BAHASA AWAL PADA ANAK - Muhassin, Mohamad (English Education: Jurnal Tadris Bahasa Inggris, 2013)
This is a critical review of article entitled Early Language Acquisition on thebook of Psychology of Language by David W. Carroll. The discussion coverstopics such as introduction, pre-linguistic communication, early phonology,acquisition of lexicon, grammar and sign language. Based on the structure andcontent analysis, the article was systematically well-arranged with an interestingpresentation by using dialogs as illustration. Moreover the article was alsoprovided with the valid and authentic data supported by logically strongargumentation and interpretation. Thus this article certainly gives a bigcontribution to the development of psycholinguistics especially in the earlyacquisition of language.